2018
DOI: 10.1038/s41467-018-07032-0
|View full text |Cite|
|
Sign up to set email alerts
|

Copper adparticle enabled selective electrosynthesis of n-propanol

Abstract: The electrochemical reduction of carbon monoxide is a promising approach for the renewable production of carbon-based fuels and chemicals. Copper shows activity toward multi-carbon products from CO reduction, with reaction selectivity favoring two-carbon products; however, efficient conversion of CO to higher carbon products such as n-propanol, a liquid fuel, has yet to be achieved. We hypothesize that copper adparticles, possessing a high density of under-coordinated atoms, could serve as preferential sites f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 51 publications
11
134
0
Order By: Relevance
“…The similar sign-reversal of  yx was observed in several other materials [25][26][27]. Focusing on this energy range, we obtain the band structure of 5SL MBT thin film and the intrinsic AHC  xy using the first-principles calculations, where the total magnetization is fixed as M Z > 0.…”
Section: The Scaling Behavior Of the Reversed Ahesupporting
confidence: 55%
“…The similar sign-reversal of  yx was observed in several other materials [25][26][27]. Focusing on this energy range, we obtain the band structure of 5SL MBT thin film and the intrinsic AHC  xy using the first-principles calculations, where the total magnetization is fixed as M Z > 0.…”
Section: The Scaling Behavior Of the Reversed Ahesupporting
confidence: 55%
“…1f). Unlike C 2 products, the formation rate of n-propanol does not show a drastic further enhancement as the O 2 ratio increases from 10 to 20%, suggesting its distinct chemistry in forming an additional carbon bond after their common rate-determining step of C-C coupling between two adsorbed CO molecules 29,31,32 . The oxygen induced enhancement of all C 2+ products is more pronounced at −0.80 V RHE ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Such nonmagnetic scatterings complicate the electronic structure and are detrimental to realizing the QHAE. Recently, Liu et al further showed that the AH resistance in (Bi 1−x Mn x ) 2 Se 3 thin film can have too components with different signs, and the surface component has a sign opposite to that of the QAH phases in Cr-or V-doped BST films [172]. Similar sign in the AH resistance was also observed in Mn-doped Bi 2 (Te 2 Se) 3 [168], Mn-doped Bi 2 Te 3 [173], and Crdoped Bi 2 Te 3 [174,175].…”
Section: Magnetically Doped 3d Tismentioning
confidence: 99%